Effect of the Layering Technique on Bond Strength and Cohesive Resistance of a Porcelain-Zirconia System - Macedo, Vanessa Cruz [UNESP]; Anami, Lilian Costa [UNESP]; Melo, Renata Marques de [UNESP]; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe (Quintessence Publishing Co Inc, 2014)
Purpose: To evaluate the influence of the number of porcelain layers on its cohesive strength and on bonding to zirconia.Materials and Methods: Y-TZP blocks were cut into 1 cm(3) specimens (n = 30). The feldspathic porcelain (V9) was applied to the zirconia in different numbers of layers up to 1 cm total thickness (n = 10): ZP1 one layer; ZP2 two layers; ZP3 three layers. Ten specimens with V9 were prepared following the same protocols of groups 1 (P1) and 3 (P3). All study specimens were sintered three times. The specimens were cut into 1 mm(2) microbars and tested under tension in a universal testing machine (0.5 mm/min). We calculated strength (sigma, in MPa) by dividing the fracture load (N) by the fractured area (mm(2)). The failure mode was classified as cohesive (used to calculate the cohesive strength, sigma(c)) or adhesive (bond strength, sigma(a)). The data were analyzed by Kruskal-Wallis and Dunn's tests (alpha = 0.05) or ANOVA and Tukey's test (alpha = 0.05), according to their distribution parameters.Results: The ZP1 group presented the highest values for cya data, compared with other groups, which were statistically similar. The predominant failure mode for the bonded specimens was cohesive. With regard to the cohesive strength (sigma(c)), ZP1 presented the highest values.Conclusion: It can be concluded that the presence of more than one porcelain layer decreases its cohesive strength and its bonding strength to zirconia.
Keywords: dental porcelain; zirconia; sintering; tensile strength